Psychological characteristics of the personality of children ill with juvenile rheumatoid arthritis and rheumatism - Bieliauskaitė, R. (Psichologija, 1984)
This work was aimed at depicting some psychological features characteristic of children ill with juvenile rheumatoid arthritis and rheumatism. Three projective tests were used: “House-Tree-Person” test, “Kinetic Family Drawing” and Rorschach test. 60 children ill with rheumatoid arthritis and rheumatism were tested. The control group consisted of 30 practically healthy children. Collected data has shown that unsociability, poverty of emotions, very high level of anxiety are characteristic of children ill with rheumatoid arthritis. Rheumatic children show high level of insecurity, hostility and antagonism in the family. Difficulties in communication, subjectively worse situation in family were characteristic of both groups of sick children.
Keywords: rheumatism; rheumatoid arthritis; personality